Revista de la Escuela Superior de Guerra ; no. 360/1965 - Escuela Superior de Guerra Tte Grl Luis María Campos (Argentina) (1965)
Ejemplar: Revista de la ESG. Año 43, no. 360 (jul.-ago. 1965). -- p. 134